Implementation of Green Entrepreneurship Through Corporate Social Responsibility Program: Asification of Clean Water Facilities in Sitada-Tada Hamlet - Siregar, Muhammad Rifai (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
The availability of clean water facilities that are easily available is a dream of rural communities throughout Indonesia, especially villages where access to clean water is limited. One of them is Sangapati Village which is located in Sitada-tada Hamlet, East Angkola District, South Tapanuli Regency. This article describes facilitating the construction of drinking water facilities, one of the alternatives to meet the drinking water and health needs of 150 people in Sitdatada Hamlet, East Angkola District, South Tapanuli Province. Based on observations, the construction of drinking water facilities uses the method of cooperation with companies in corporate social responsibility programs. With the results achieved in this activity, it is easier for the people of Sitada-tada hamlet to get clean water to meet their daily needs. The availability of clean water facilities can improve the quality of life for the people of Sitada-tada hamlet and reduce the risk of various diseases.